2019
DOI: 10.21463/jmic.2019.08.2.06
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Tourism Development on Community Well-being in Langkawi: The Case of Kampung Padang Puteh, Mukim Kedawang

Abstract: Tourism has assisted the development of environmental, economic, social and cultural aspects of island communities. While there are some previous studies on the impacts of tourism development across Langkawi, it is necessary to consider the impacts of tourism development on individual island communities. Kampung Padang Puteh, Mukim Kedawang, Langkawi is located on the route between the island's main tourism attraction areas, Pantai Cenang and Pantai Tengah (which are highly affected by tourism activities). Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
(37 reference statements)
0
4
0
2
Order By: Relevance
“…Subjective wellbeing refers to an individual's overall evaluation and perception of wellbeing, happiness, life satisfaction, and fulfilment. In the context of community-based tourism in Batu Puteh, Kinabatangan, Borneo, subjective wellbeing can be influenced by various factors related to value co-creation and community participation (Ibrahim et al, 2019). These factors include the level of community involvement and empowerment, the economic benefits generated from tourism activities, the preservation and promotion of cultural heritage, and the overall quality of the tourism experience for both locals and tourists.…”
Section: Subjective Wellbeingmentioning
confidence: 99%
“…Subjective wellbeing refers to an individual's overall evaluation and perception of wellbeing, happiness, life satisfaction, and fulfilment. In the context of community-based tourism in Batu Puteh, Kinabatangan, Borneo, subjective wellbeing can be influenced by various factors related to value co-creation and community participation (Ibrahim et al, 2019). These factors include the level of community involvement and empowerment, the economic benefits generated from tourism activities, the preservation and promotion of cultural heritage, and the overall quality of the tourism experience for both locals and tourists.…”
Section: Subjective Wellbeingmentioning
confidence: 99%
“…The younger generation is a significant component of communities and stakeholders, and they should be able to participate in the planning and development of how local goals are managed. Rami et al (2019) and Ibrahim et al (2019) found that the development of local tourism can improve the community's welfare. It is consistent with the community's growing socioeconomic status, employment, income, and language proficiency (Nordin et al, 2020).…”
Section: Correlation Of Cbt With Sustainable Development To Improve C...mentioning
confidence: 99%
“…Although it has many positive impacts, local tourism has challenges. Understanding the extent of community welfare during tourism development is essential, a critical element of realizing a sustainable society (Ibrahim et al, 2019;Rami et al, 2019). Potential benefits of rural tourism include employment, a broader economic basis, social development, communal welfare, and the revitalization of local crafts (Nicolaides, 2020).…”
Section: Correlation Of Cbt With Sustainable Development To Improve C...mentioning
confidence: 99%
“…Dalam penelitiannya Ibrahim et al (2019) menjelaskan bahwa pengembangan pariwisata lokal dapat meningkatkan kesejahteraan masyarakat, masyarakat setempat ditemukan telah meningkatkan tingkat sosial ekonomi mereka melalui kesempatan kerja; pendapatan tambahan dan keterampilan bahasa. Hasil penelitian dari Nordin et al (2020) menyatakan bahwa Pembangunan pariwisata lebih banyak memiliki dampak positif dari pada dampak negatif, adanya pembangunan pariwisata ini dinilai dapat meningkatkan kualitas hidup masyarakat.…”
Section: Kajian Literaturunclassified
“…Dalam penelitiannya Nordin et al (2020) juga menemukan pengaruh manfaat sosial budaya, manfaat ekonomi, biaya ekonomi, dan manfaat lingkungan memiliki hubungan yang signifikan dengan kualitas hidup, adanya temuan ini sangat penting bagi perencanaan dan pengembangan dalam merencanakan pembangunan pariwisata yang strategis dan berkelanjutan di destinasi pariwisata. Meski memiliki banyak dampak positif, pariwisata lokal ini juga memiliki tantangan, oleh karena itu sangat penting untuk memahami sejauh mana kesejahteraan masyarakat di tengah pembangunan pariwisata yang merupakan elemen kunci dalam mewujudkan masyarakat yang berkelanjutan (Ibrahim et al, 2019).…”
Section: Kajian Literaturunclassified